2020
DOI: 10.2147/cmar.s227628
|View full text |Cite
|
Sign up to set email alerts
|

<p>Associations Between miRNAs and Two Different Cancers: Breast and Colon</p>

Abstract: Objective: Screening approaches using microRNAs (miRNAs) have been gaining increased attention owing to their potential applications in the diagnosis, prognosis, and monitoring of cancer, because aberrant miRNA expression plays a role in the development and advancement of malignancies. The objectives of this study were to characterize mir21, miR31, mir143, mir145, and control RNU43, which are differentially expressed in peripheral blood mononuclear cells (PBMCs) of breast and colorectal cancer patients, compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In a previous study, the expression level of miR-205 increased during the pathogenesis in Escherichia coli- infected bovine mastitis ( 11 ), indicating that the regulatory effects of miRNA might be different in mastitis with varying types of bacterial infection. Kundaktepe et al ( 44 ) reported that the expression level of miR-143 in peripheral blood mononuclear cells of breast cancer patients significantly decreased, which could be used as a breast cancer biomarker. In addition, human miR-143 can inhibit breast cancer cell proliferation and metastasis by regulating the gene expression of MAPK3 ( 45 ), MAPK7 ( 46 ), MYBL2 ( 47 ), CD44 ( 48 ), and ERBB1 ( 49 ) in cooperation with protein levels and phosphorylation status of AKT, Wnt/β-catenin, SAPK/JNK, and FAK of NF-κB signaling pathways and multiple oncoproteins in JAK/STAT signaling pathway ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the expression level of miR-205 increased during the pathogenesis in Escherichia coli- infected bovine mastitis ( 11 ), indicating that the regulatory effects of miRNA might be different in mastitis with varying types of bacterial infection. Kundaktepe et al ( 44 ) reported that the expression level of miR-143 in peripheral blood mononuclear cells of breast cancer patients significantly decreased, which could be used as a breast cancer biomarker. In addition, human miR-143 can inhibit breast cancer cell proliferation and metastasis by regulating the gene expression of MAPK3 ( 45 ), MAPK7 ( 46 ), MYBL2 ( 47 ), CD44 ( 48 ), and ERBB1 ( 49 ) in cooperation with protein levels and phosphorylation status of AKT, Wnt/β-catenin, SAPK/JNK, and FAK of NF-κB signaling pathways and multiple oncoproteins in JAK/STAT signaling pathway ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, miR-21 is overexpressed in breast cancer patients promoting cell proliferation, migration, and invasion and thereby acts as oncomiR, 49 while miR-31, miR-143, and miR-145 are known to be under-expressed in breast cancer patients inhibiting cell proliferation. 99 , 100 However, in colorectal cancers, the expression of miR-21 and miR-31 shows different behavior where overexpression of those miRNAs can be seen in colorectal patients promoting inflammation-associated tumorigenesis. 88 In such a situation, it is worth counting the synergistic effects of miRNAs in such cancer types that can occur as second de novo malignancy in cancer survivors.…”
Section: Association Between Breast and Colorectal Cancersmentioning
confidence: 99%
“… 88 In such a situation, it is worth counting the synergistic effects of miRNAs in such cancer types that can occur as second de novo malignancy in cancer survivors. 100 Figure 2 illustrates the possible connection to the occurrence of colorectal cancer in females with a history of breast cancer.
Figure 2 Occurrence of colorectal cancer in female breast cancer patients/survivors.
…”
Section: Association Between Breast and Colorectal Cancersmentioning
confidence: 99%
“…Growing evidence indicates that circulating miRNAs are noninvasive molecular markers and predictors of disease activity [8]. MiR-21 is involved in different types of tumors [9,10] and diseases related to increased oxidative stress and inflammation [11,12]. COPD is a systemic inflammatory syndrome [13] and systemic miR-21 and IL-8 are both increased in COPD, acting as indicators of COPD severity [14].…”
Section: Introductionmentioning
confidence: 99%